The dragons of Nova - Kova, Elise (Kova, Elise. Loom saga, 2016)
Cvareh returns home to Nova with genius crafter Arianna in tow. The mercurial inventor possesses all the Xin family needs to turn the tides of a centuries-old power struggle, but she is also working toward exacting vengeance against the traitor who killed everything and everyone she once loved. Before she's ready, the Crimson Court exposes her shadowed past and reveals something even more dangerous sparking between her and Cvareh. While Nova is embroiled in blood sport and political games, the rebels on Loom prepare for an all-out assault on their Dragon oppressors. Florence unexpectedly finds herself at the forefront of change, as her unique blend of skills--and quick-shooting accuracy--makes her a force to be reckoned with. For the future of her world, she vows vengeance against the Dragons. But before the rebellion can rise, the Guilds must fall. --